1967
DOI: 10.2136/sssaj1967.03615995003100060022x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Effects on Cotton: I. Vegetative and Fruiting Characteristics

Abstract: A series of N fertilization experiments was conducted over three growing seasons, at three elevations, utilizing two varieties of ‘Acala’ cotton (Gossypium hirsutum) on two soil types. The treatments consisted of various rates and timing of N fertilizer applications. Data indicated that N deficiency at early growth stages limited development of vegetative branches, internode elongation, and fruiting, particularly in “one‐peak” flowering areas. Cotton plants can compensate by increased fruiting in longer season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Nitrogen fertilizer has been shown to increase leaf number and leaf area (Bondada et al, 1996), plant height (Gardner and Tucker, 1967), number of nodes (Jackson and Gerik, 1990), Bronson et al, 2003). Zhao et al (2010) found that the seasonal pattern of N concentrations derived from the entire plant canopy was consistent to the analysis obtained from uppermost, fully expanded leaves.…”
Section: Introductionmentioning
confidence: 57%
“…Nitrogen fertilizer has been shown to increase leaf number and leaf area (Bondada et al, 1996), plant height (Gardner and Tucker, 1967), number of nodes (Jackson and Gerik, 1990), Bronson et al, 2003). Zhao et al (2010) found that the seasonal pattern of N concentrations derived from the entire plant canopy was consistent to the analysis obtained from uppermost, fully expanded leaves.…”
Section: Introductionmentioning
confidence: 57%
“…[4] From germination to cotyledonary growth, nutrient demand is not high due to limited root exploration and photosynthesis capability. [7] Lay-by nitrogen applications can remedy nitrogen deficiencies before significant yield loss, but 744 Rinehardt et al If labile nitrogen is exhausted from the soil during this period, development will be limited and yield potential will be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, even though there were no significant differences for the first productive PP (Table 5), these results seem to be partially related to the lower accumulated boll number at early fruiting sites. Usually, increased N rates intensify vegetative growth (Gardner and Tucker, 1967;Gerik et al, 1994;Zhou and Yin, 2014), which may result in a lower yield proportion at first PPs. This response was clearly observed in Itapeva, where the two highest N rates resulted in at least 3.19 more bolls per plant compared with the two lowest ones above the 16th PP (Table 6).…”
Section: Discussionmentioning
confidence: 99%